A termografia no apoio ao diagnóstico de lesão muscular no esporte - Bandeira, Fábio Henrique (2013)
Introduction: Muscle lesions are very common and usually move away athletes from practicing sports, becoming also a nuisance to the clubs. Due to its characteristics, rugby is one of the sports where lesions on athletes happen very often. The muscle lesion presents a thermal variation in the affected area, causing a local increase of temperature. Supposedly these areas can be evaluated through the measurement of temperature. Objective: The general objective of this study was to analyze the use of thermography as a method of support on the diagnosis of muscle lesions in rugby athletes during training activities and games. Methodology: participating in this study were, 21 male rugby athletes, aged between 19 and 31 years old, registered with the Brazilian Rugby Confederation, belonging to the adult categories at a professional level of a national team, who perform daily training for over two years and who have participated for at least 40 minutes of training or of an official rugby match. Twice there were collections of blood samples so the serum CK could be identified, expressed in IU/L; one collection 48 hours after training and another 48 hours after a game. The infrared images of the athletes were obtained, these being previously instructed on the procedures to be followed on the day of the exam. On collection the athletes were dressed only with their underwear, standing up, for 30 minutes with muscle at rest in a chamber which adapts to the temperature, with temperature and humidity controlled between 22° and 23 °C and 45 and 50% respectively. Images were collected from the upper body (superior) and upper-legs (inferior), from anterior and posterior sides. The images were analyzed systematically and by inspection. Results: The systematic analysis revealed that there is no correlation between de CK variation and temperature variation in muscles analyzed. The average temperature in the selected areas of all muscles were higher when the CK was higher, however, the variation of CK did not show any significant positive correlation with the temperature in the same situations. When separating the participants who presented a variation higher than 50% on the serum CK level between moments of higher and lower concentration, the left upper body muscles, left rectus femoris and left semitendinosus presented the biggest differences with p-value of 0.037, 0.057 and 0.045, respectively. The left body hemisphere showed a bigger difference in temperature when compared with the right body hemisphere. The evaluation by inspection showed that the anterior superior and posterior inferior regions presented 13 athletes with increased temperature higher than 0.6 °C coinciding with an increase of the serum CK. The posterior superior and the anterior inferior presented 11 athletes with temperature variation higher than 0.6 °C between the moments of higher and lower CK. Conclusions: It is possible to conclude that thermography can and should be utilized as a supporting method to diagnose muscle lesion in athletes, recommending the use of the visual analysis by inspection.